Analysis of Character Education Value on English Textbook Students Grade Seventh Of SMPN 10 Parepare - Anwar; Nurul Hirdayu; Wahyu Hidayat (Inspiring: English Education Journal, 2022)
Character values should be taken into consideration in teaching and learning material. Textbook is one of media that can be used in teaching character education. The purpose of this research were to find out what character education values in English textbook students for grade seventh entitled “When English Rings A Bells”. This research was focused on revealing the Character Educational Value based on The Ministry of Education and Culture within the textbooks. This research used content analysis study to know the implemented EFL textbook. The procedure in data collection were table checklist and documentation. Technique of data analysis is data collection, data reduction, data display and conclussion. Based on the results of the analysis and discussion that has been described shows that Character Educational value in English Textbook entitled When English Rings A Bell, The value of Friendship/Communicative was the most Common Value With 21%. Then it was followed by Independent with 17%. The other valaue such as Religious 12%. Hard work value contains 7%. Discipline and Social Care value with 5%. Curiosity value with 4.6%. Creativity, Nationalism, and Appreciation Achievement with 4.1%. Enviromental Awareness and Honesty values with 3.5%. Reading Interest value with 2.5%. Tolerance value with 2.0%.Patriotism and Responsibility value contains 1.02%. The smallest were Love and Peace value with 0.5%. These findings lead to the conclusion that the textbook contain character educational values and upcoming for the future textbooks must pay a lot more attention to the character values. Keywords: Character Education, Value, Textbook Analysis, English textbook, 2013 Curriculum,